ANALISIS MUSIK GONDANG BATARA GURU DALAM UPACARA ADAT SUKU BATAK TOBA DI SINTANG KALBAR - Ambarita, David Morison; Ismunandar, Ismunandar; Silaban, Christianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research based on the lack of interest for traditional art which is an ancestors heritage and the need for some effort to learn and preserve traditional music. One of traditional art from Batak Toba tribe wich exist in Sintang, West Kalimantan is Gondang Batara Guru in wedding ceremonial of Batak Toba tribe in Sintang West Kalimantan. The purpose of this research is to describing shape and music melody of Gondang Batara Guru music in wedding ceremonial of Batak Toba tribe in Sintang West Kalimantan. The method that used in this research is qualitative descriptive method and use musicology approach. Data contained in this research is the result of direct observation and interview with informant about shape and melody of Batara Guru music. Along with the times, and religion comes, Gondang Batara Guru music is more focused as dance music and to entertain in wedding ceremonial and as the thanks for the god ceremony in Batak Toba tradition especially Music Batara Guru music in wedding ceremonial in Sintang West KalimantanÂ Keywords: Analysis, Gondang Batara Guru Music, Batak Toba Tribe, Sintang, West Kalimantan.Â